Analisa Performansi Lora Pada Sistem Absensi Mahasiswa - Yofan Hakiki; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Attendance lists are very much needed in lectures. The presence system using fingerprints was chosen because it has advantages, namely Perennial Nature, Immutability, Individuality. Thepresence system device uses the FPM10A fingerprint sensor, Arduino uno as a microcontroller and LoRa as a transceiver module. The LoRa module was chosen because it has advantages, namelygeolocation, low power consumption, can transmit a maximum signal of 100 KM and is equipped with end-to-end AES128 encryption. The test scenario is carried out in two conditions, namely Lineof Sight (LOS) and Non-line of Sight (NLOS) conditions which are divided into 5 test points, namely 50m, 100m, 150m, 200m and 250m. The spreading factor used is SF7 with a bandwidth of 125 KHzand a coding rate of 4/5. The bitrate value is 5496 bits / sec. The best RSSI value in LOS conditions is -73.40 dBm and NLOS conditions is -87.90 dBm. The best delay value in LOS conditions is0.03713 s and NLOS is 0.0371192 s. The best transfer rate in the LOS condition is 0.029213 bits / sec and the NLOS condition is 0.29214 bits / sec. The best throughput in the LOS condition was0.23370% and the NLOS condition was 0.2336%. In the LOS condition, the LoRaTM modulation is capable of receiving data up to 250m while the LoRaTM modulation NLOS condition is capable of receiving data up to 250m. Energy usage when sending data is 0.001066397 J, when receiving data is 0.000682536 J. When the sending device is willing to use energy of 5.08296614 J and thereceiving device is 3.011387426 J.Keyword: presence, LoRa, Modulation